Methodological Prolegomena to Proclus. Reference Text “About Plato’s Theology” (I, 5.6-8.15) - Terezis, Christos; Deli, Georgia (Études helléniques / Hellenic Studies, 2001)
Proclus was a prominent Neo-Platonic philosopher who lived in the Vth century AD (410-485). Born in Constantinople and educated in Alexandria, Proclus was one of the last leaders of the Platonic Academy before its closing, in 529, by Justinian and one of the last philosophers of Antiquity. Among his works, noteworthy is his About Plato’s Theology (Peri tes kata Platona theologias) along with his commentaries on Plato’s Timaeus, Republic and Parmenides as well as his comments on Euclid’s First Book and Ptolemy’s Tetrabiblos. This brief article endeavors to explain, through the “appropriate linguistic material”, a few key concepts of Proclus’s hierarchical system as it relates to the “Patonic theology”.